Answer:
x³ - (√2)x² + 49x - 49√2
Step-by-step explanation:
If one root is -7i, another root must be 7i. You can't just have one root with i. The other roos is √2, so there are 3 roots.
x = -7i is one root,
(x + 7i) = 0 is the factor
x = 7i is one root
(x - 7i) = 0 is the factor
x = √2 is one root
(x - √2) = 0 is the factor
So the factors are...
(x + 7i)(x - 7i)(x - √2) = 0
Multiply these out to find the polynomial...
(x + 7i)(x - 7i) = x² + 7i - 7i - 49i²
Which simplifies to
x² - 49i² since i² = -1 , we have
x² - 49(-1)
x² + 49
Now we have...
(x² + 49)(x - √2) = 0
Now foil this out...
x²(x) - x²(-√2) + 49(x) + 49(-√2) = 0
x³ + (√2)x² + 49x - 49√2
Which color do most children like best? ask 10 children make tally mark for each child's answer
there
Answer:
No, it isn't.
Step-by-step explanation:
Pythagorean theorem is x^2 + y^2 = z^2.
6^2 + 8^2 = 9^2
36 + 64 = 81
100 = 81
So, it isn't.
Answer:
10x - 3y = -109 .
Step-by-step explanation:
x^2 + y^2 = 109
Implicit Differentiation:
2x + 2y.y' = 0
y' = -2x/2y = -x/y
So at the point (-10,3) the gradient of the tangent is -(-10)/3 = 10/3.
Equation of the tangent:
y - y1 = m(x - x1)
y - 3 = 10/3(x + 10)
y - 3 = 10/3 x + 100/3
3y - 9 = 10x + 100
-109 + 3y = 10x
10x - 3y = -109